1999
DOI: 10.1021/bi990758z
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structure of the Asn276Asp Variant of the Escherichia coli TEM-1 β-Lactamase:  Direct Observation of Electrostatic Modulation in Resistance to Inactivation by Clavulanic Acid,

Abstract: The clinical use of beta-lactam antibiotics combined with beta-lactamase inactivators, such as clavulanate, has resulted in selection of beta-lactamases that are insensitive to inactivation by these molecules. Therefore, therapeutic combinations of an enzyme inactivator and a penicillin are harmless for bacteria harboring such an enzyme. The TEM beta-lactamase variants are the most frequently encountered enzymes of this type, and presently, 20 variants are designated as inhibitor-resistant TEM ("IRT") enzymes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 42 publications
3
64
0
Order By: Relevance
“…Alternatively, the imine 2 could be directly hydrolyzed to yield the aldehyde 5 and hydrate aldehyde 6. This pathway is entirely consistent with that proposed for the inhibitor-resistant TEM-33 (M69L) and N276D-substituted enzymes (10,11). Our kinetic data for tazobactam and clavulanic acid suggest that the rate that each intermediate is formed and the number of branch points differ for each inhibitor.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Alternatively, the imine 2 could be directly hydrolyzed to yield the aldehyde 5 and hydrate aldehyde 6. This pathway is entirely consistent with that proposed for the inhibitor-resistant TEM-33 (M69L) and N276D-substituted enzymes (10,11). Our kinetic data for tazobactam and clavulanic acid suggest that the rate that each intermediate is formed and the number of branch points differ for each inhibitor.…”
Section: Discussionsupporting
confidence: 88%
“…The water molecule may also function with Lys-73 in a coordinated proton shuttle and may substitute for the Ser-130 in protonating the ␤-lactam nitrogen (26,27). In the x-ray structures of the inhibitor resistant TEM-30 (R244S) and TEM-84 (N276D), the relocation of a conserved water plays a crucial role in the binding affinity of inhibitors (10,12). The molecular modeling studies of the E166N amino acid substitution of TEM-1 ␤-lactamase revealed the movement of a catalytic water molecule was essential in modification of the substrate profile (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In classes A and C ␤-lactamases, the catalytic water molecule is anchored through a hydrogen bond network in an optimum position for nucleophilic attack on the carbonyl carbon of the acyl-enzyme species. The position of this water molecule is crystallographically conserved (31,36,41) unlike in class D enzymes (42)(43)(44). Perturbation of the hydrogen bonding network of this water molecule or the physical displacements of the water molecule by the steric bulk of the C-6 side chains of a ␤-lactam are possible mechanisms to render the ␤-lactamase deacylation-deficient (20,(45)(46)(47).…”
Section: Mechanism Of ␤-Lactammentioning
confidence: 99%
“…To date, atomic resolution structures of five IRT mutants have been determined (9)(10)(11). The Arg244Ser substitution found in the TEM-30 mutant results in displacement of a water molecule involved in the inactivation chemistry of clavulanate (3,10).…”
mentioning
confidence: 99%